Pengaruh Frekuensi Antenatal Care Terhadap Kepatuhan Mengkonsumsi Tablet Fe Pada Ibu Hamil di Puskesmas Meukek Tahun 2023 - Risma Yunita; Ika Damayanti Sipayung; Sri Rezeki (The Journal General Health and Pharmaceutical Sciences Research, 2023)
Anemia in pregnancy may have a bad effect on the mother and fetus. The anemia occurred in a pregnant mother will increase the risk of mortality of the mother compared to those without anemia. The presence of iron-deficiency anemia during pregnancy could be identified through ANC examination through the admission of iron (FE) tablet supplementation which is very vital for the increase of hemoglobin (Hb) of the blood of the pregnant mothers. According to the research conducted in Aceh Regency, any pregnant mother who does not receive a standard ANC service could result in inconstancy of FE tablet consumption, which later will increase the risk of anemia.To find out the effect of antenatal care frequency on the constancy of FE tablet consumption on pregnant mothers in Puskesmas (Community Health Center) of Meukek. The research design used in this research is the quantitative research with cross-sectional approach. The sampling was conducted by using total sampling method with a total of 40 pregnant mothers as the respondents. The instruments used in this research are the KIA card for pregnant mothers on the antenatal care visit variable and the questionnaire on the constancy of FE tablet consumption variable. The bivariate analysis was conducted using Chi-square test.The x2 value obtained is 9,401 and the p value = 0,002 (p<0,05) and OR=17,889 (95% CI [1,919-166,782), which showed that there is an effect of the antenatal care frequency on the constancy of Fe tablet consumption on the 3rd trimester pregnant mothers.The antenatal care frequency has an effect on the constancy of Fe tablet consumption on the 3rd trimester pregnant mothers.